Quality and Reliability Analysis of YouTube as a Source of Patient Information on de Quervain's Tenosynovitis - Kim, Jason H.; Hoy, John F.; Shuman, Samuel L.; Ahmad, Farhan; Simcock, Xavier C. (Journal of Wrist Surgery, 2023)
Purpose This study seeks to evaluate the quality and reliability of information regarding de Quervain's tenosynovitis on YouTube.Materials and Methods A search on the YouTube was performed using the keywords de Quervain's tenosynovitis, and the first 50 videos were evaluated. Video characteristics including views, content type, and video upload source were recorded. Video reliability was assessed using the Journal of the American Medical Association (JAMA) benchmark criteria. Video quality was assessed using the Global Quality Score (GQS) and a novel de Quervain's Tenosynovitis-Specific Score (DQT-SS).Results The total number of views for all videos evaluated was 5,508,498 (mean, 110,169.96 ± 155,667.07). Video reliability and quality metrics were low, with a mean JAMA score of 2.17 ± 0.82 out of 4, a mean GQS of 2.49 ± 1.28 out of 5, and a mean DQT-SS of 4.53 ± 2.35 out of 11. Significant between-group effects were found for the video source and DQT-SS (p = 0.027), as well as between content type and JAMA score (p = 0.027), GQS (p = 0.003), and DQT-SS (p = 0.003). Positive independent predictors of DQT-SS included video duration in seconds (β = 0.391) and disease-specific information content type (β = 0.648).Conclusion Videos on YouTube regarding de Quervain's tenosynovitis were frequently viewed; however, the information present was of low quality and reliability. Physician-uploaded videos had the highest mean JAMA scores, GQS, and DQT-SS, but had the second-lowest mean number of views of video sources. Patients should receive proper in-office education and be directed toward reputable resources for their orthopaedic conditions.
Keywords: de Quervain's tenosynovitis; internet; YouTube; education; quality